Permanent employment dressed up as Fixed-Term Contract: a review of Ahmad Zahri Mirza Abdul Hamid v Aims Cyberjaya Sdn Bhd - Ali Mohamed, Ashgar Ali (LexisNexis Malaysia sdn Bhd, 2020)
The recent Federal Court’s decision in Ahmad Zahri Mirza Abdul Hamid v Aims Cyberjaya Sdn Bhd reaffirmed the security of tenure of employees in the private sector in Malaysia and the earlier decisions of the superior courts in Hong Leong Equipment Sdn Bhd v Liew Fook Chuan & Anor,2Ang Beng Teik v Pan Global Textile Bhd, Penang,3and The New Straits Times Press (Malaysia) Bhd v Chong Lee Fah,4 among others were cited with approval. This right however has to be balanced with the employer’s managerial prerogative to make commercial decisions for reasons of better management of their business or establishment.5 The employer is entitled to decide on the need of labour to carry out the day-to-day management of the company and this include hiring workers on permanent or temporary basis such as fixed term engagement or a fixed duration. There are several reasons why the employer engages workers on a fixed term basis such as seasonal work, to fill gaps caused by temporary absence of a permanent staff on long term leave and for the performance of specific task, among others. It is common for the construction industry to hire workers for a specific period which is project-based. Likewise, the expatriates or migrant workers are hired on a fixed term duration.This prerogative is however subject to the rule that the employer must act bona fide and in the interest of the business as a whole. The emphasis is that the recourse to a fixed term engagement must genuinely relate to the operational requirements of the undertaking or the establishment of the employer. This is primarily to ensure that the employer does not use fixed term engagement to deprive the workers of their statutory protection and benefits such as retrenchment benefits and the unfair dismissal claim, among others. This is reiterated by the International Labour Organisation’s (‘ILO’) Convention No 158 of 1982 which provides inter alia, that ‘adequate safeguard’ is required to prevent fixed-term contract from being the means of depriving workers of their job security. In other words, a fixed term engagement must be for genuine commercial reasons and not motivated with victimisation or unfair labour practice.In a genuine fixed term contract, both the parties have agreed that the contract would terminate lawfully at the end of the stipulated time-frame and such termination will not constitute a dismissal from employment. In such situation, there is neither a resignation nor termination and the company is under no obligation to state the reasons for the non-renewal of the contract. The question whether a ‘fixed term contract’ is genuine or sham is both a question of law and fact. No two sets of facts are alike. Therefore, each case has to be decided purely on the facts of the individual case. The burden is on the employer to establish that the recourse to a fixed term engagement was genuinely related to their business establishment or undertaking.In relation to a reference under s 20 of the Industrial Relations Act 19676 (‘the IRA’) for dismissal without just cause or excuse, the Industrial Court will consider, inter alia, whether the contract was a genuine fixed term contract or a permanent employment guised as a fixed-term contract. If the court finds the contract as a genuine fixed term, in the sense that there were no ulterior motive or victimisation on the part of the company in employing workers on a fixed term basis, the court would dispose of the dispute without going into the merits of the case namely, whether there was a dismissal and if so, whether it was with just cause or excuse.7 However, if the court declares the fixedterm contract as not genuinely related to the operational requirement or undertaking or establishment of the employer, the court will hold the employee’s engagement as on a permanent basis and that his dismissal was without just cause or excuse.In the past few years, numerous cases involving the non-renewal or extension of fixed term contract had successfully been litigated in the Industrial Court. The emphasis is that the employer’s commercial reasons to engage workers on a fixed term duration must genuinely relate to their business needs. If a fixed term engagement was not bona fide or genuine, the court would pierce such arrangement and thereafter hold the contract as a permanent employment ie, a permanent employment guised or dressed up as fixed term contract. Having said the above, this article discusses the fixed term engagement of workers with special reference to the recent Federal Court’s decision in Ahmad Zahri Mirza Abdul Hamid v Aims Cyberjaya Sdn Bhd. In this case, the Federal Court held, inter alia, that all workers, without distinction whether they are local or migrants, should be treated with fairness, dignity and equality. It was further stated that citizenship of an employee has no bearing in deciding whether the applicant was in permanent employment or under a fixed term contract.